Innovation outlook : ocean energy technologies. (International Renewable Energy Agency, 2020)
Oceans contain vast renewable energy potential - theoretically equivalent to more than double the world's current electricity demand. Nascent ocean energy technologies could cut carbon dioxide (CO2) emissions from power generation and help to ensure a sustainable, climate-safe energy future. Alongside other offshore renewable energy technologies, ocean energy - including wave, tidal, salinity gradient and ocean thermal energy conversion technologies - forms a crucial component in the world's emerging blue economy. This outlook from the International Renewable Energy Agency (IRENA) examines the status and prospects of ocean energy technologies. It examines the operating principles, current installed capacity and projected project pipeline, along with markets and theoretical energy potential for each ocean energy type. The report also identifies challenges and offers recommendations to accelerate the deployment and commercialisation of each technology. IRENA's Innovation Outlook series analyses rapidly emerging renewable energy technologies (RETs) and examines ways to enhance their competitiveness. Each outlook identifies technology-, industry- and policy-related challenges and assesses the potential breakthroughs needed to accelerate the uptake.